2021
DOI: 10.1136/rmdopen-2020-001497
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence optical imaging: ready for prime time?

Abstract: The novel technique of fluorescence optical imaging (FOI, Xiralite), which is approved in the European Union and the USA for clinical use, has been the object of studies since 2009. Indocyanine green-based FOI can demonstrate an impaired microcirculation caused by inflammation in both hands in one examination. Several studies have investigated FOI for detection of joint inflammation by comparing FOI to magnetic resonance imaging (MRI) and/or musculoskeletal ultrasound (MSUS). The results have shown a generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 32 publications
(59 reference statements)
0
27
0
17
Order By: Relevance
“…The examination of both hands lasts 6 min and one image per second is recorded, resulting in a total of 360 images. A recently published comprehensive review summarized the role of FOI in research and clinical practice and outlined how FOI can complement our current imaging repertoire in rheumatology [ 87 ]. While some studies have compared FOI to MRI and MSUS in patients with RA and demonstrated that it is a useful technique and can be used to distinguish RA from osteoarthritis, as of yet, there are no published studies on the use of FOI in SLE [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The examination of both hands lasts 6 min and one image per second is recorded, resulting in a total of 360 images. A recently published comprehensive review summarized the role of FOI in research and clinical practice and outlined how FOI can complement our current imaging repertoire in rheumatology [ 87 ]. While some studies have compared FOI to MRI and MSUS in patients with RA and demonstrated that it is a useful technique and can be used to distinguish RA from osteoarthritis, as of yet, there are no published studies on the use of FOI in SLE [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recently published comprehensive review summarized the role of FOI in research and clinical practice and outlined how FOI can complement our current imaging repertoire in rheumatology [ 87 ]. While some studies have compared FOI to MRI and MSUS in patients with RA and demonstrated that it is a useful technique and can be used to distinguish RA from osteoarthritis, as of yet, there are no published studies on the use of FOI in SLE [ 87 ]. However, initial data comparing FOI and MSUS images of the hands of a patient with ‘Rhupus’ suggest that FOI may be a useful technique for detecting joint manifestations in patients with ‘Rhupus’ and possibly SLE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since MRI can visualize and localize inflammation without the need for radionuclide injection and ionizing radiation exposure, the scope of PET/CT will likely not extend beyond specific research applications 91 . As a comparatively new technique in this field, FOI requires further investigation to demonstrate its value 92 …”
Section: Discussionmentioning
confidence: 99%
“…91 As a comparatively new technique in this field, FOI requires further investigation to demonstrate its value. 92 As the aim of this study was to scope for features and provide a terminology for further investigation, additional studies are needed to determine the clinical utility of the glossary. The notable inter-and intra-method discrepancies of microvascular changes, in particular regarding 9 capillaroscopic features, warrant a critical reassessment before psoriatic activity can be quantified reliably using capillary metrics.…”
Section: Clinical Relevance Of Non-invasive Imagingmentioning
confidence: 99%
“…PsA is a seronegative arthritis with late pathognomonic signs in conventional radiology. Newly developed imaging techniques may be more sensitive for the early diagnosis of PsA [7]. However, to a certain degree, the diagnosis of PsA depends on the presence of diseased skin or nail manifestations on the patient or in the family history, as proposed by the classification criteria for PsA (CASPAR) [8].…”
Section: Introductionmentioning
confidence: 99%